2014
DOI: 10.1007/s10815-014-0204-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel universal multiplex PCR improves detection of AZFc Y-chromosome microdeletions

Abstract: Purpose To determine the frequencies and the characteristics of Y chromosome microdeletions (pl) in infertile men from central China to perform appropriate therapeutic choices by updated multiplex-PCR. Methods In this study, we established a novel universal primer-multiplex-PCR (U-M-PCR) method to overcome the disadvantages of traditional multiplex PCR (M-PCR). We chose 15 sequence-tagged sites (STS) for detection of Y chromosome microdeletions. 540 infertile male patients and 100 healthy male controls were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…This variation depends on mosaic cell line of 45,X and also the percentage of SRY-positive cells in the gonads [7]. As a result, in the mosaic patient, dominant cell line seem to be influencing the sex phenotype irrespective of the proportion of the Y-cell line [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variation depends on mosaic cell line of 45,X and also the percentage of SRY-positive cells in the gonads [7]. As a result, in the mosaic patient, dominant cell line seem to be influencing the sex phenotype irrespective of the proportion of the Y-cell line [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide all chromosomes were also identified by Agilent SurePrint G3 Human CGH 60K MicroArray Platform (Agilent Technologies, CA, United States) chromosomal microarray analysis for the advance detection of affected gene or genes in the chromosomal break points for the presented case( Figure 3). After using of all comparable techniques the current infertile man wad diagnosed as mos46,X,idic(Y)(pter->q12::q12->pter) (92)/45,X (8).Some eigth sequence-tagged sites (STS) sY85, G34990, sY133, sY127, sY254, sY255 were deleted after multiplex fragman PCR analysis ( Figure 2B). …”
Section: Case Reportmentioning
confidence: 99%
“…Generally, identifying and diagnosing microdeletions can help physicians to prevent patients from undergoing experimental and often costly treatments for infertility and also provides information that makes it possible to find sperm in azoospermic men's testes and freeze oligospermic men's sperm ( 7 ). More clearly, it is highly important to investigate these microdeletions to detect microdeletions in question before undergoing ICSI, contribute to treatments for infertility, conduct genetic experiments on azoospermic and oligospermic men, screen sperm before donating it to the sperm bank and population genetics, and enhance the speed of discovering and identifying the Y chromosome microdeletions in different countries and regions ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…This classification is based on structural observation which found that AZFb and c partially overlapped. This region of overlap is now called azoospermic factor of region "d" AZFd and is located between AZFb and AZFc [84,85]. Depending on the location of the AZF microdeletion, the phenotypes vary from mild (<15 × 10 6 spermatozoa × mL −1 ) or severe (<5 × 10 6 spermatozoa × L −1 ) oligozoospermia to azoospermia (complete lack of sperm cells in ejaculation) [19,81].…”
Section: Microdeletions In the Azoospermic Factor Azf Regionmentioning
confidence: 99%